ALGORITHM FOR INTERCEPTION AND DESTRUCTION OF ENEMY UAVS BY ARTIFICIAL INTELLIGENCE-CONTROLLED DRONES-LIQUIDATORS - AFTANAZIV, IVAN; KORENDII, VITALIY; STROHAN, ORYSIA; FOSTYAK, VITALIY (Herald of Khmelnytskyi National University. Technical sciences, 2025)
To increase the defense capability of settlements and their infrastructure facilities, as well as the defense capability of military units of Ukraine due to reliable resistance to attacks by enemy sabotage, reconnaissance and strike unmanned aerial vehicles (UAVs), an improved scheme for determining the exact coordinates of objects moving in the airspace by means of kinematic design has been created. A methodology for determining the trajectories of spatial movements of moving objects, their speeds and coordinates by means of kinematic design has been created. Including, principle schemes for the optimal placement of search radar equipment for the successful detection of enemy aircraft with the aim of their subsequent destruction have been developed. According to the proposed scheme, the determined coordinates and parameters of the spatial movements of enemy UAVs are directed to the support command posts equipped with liquidator drones (kamikazes) and small arms or to the control points of anti-aircraft missile systems (AMS), which eliminate these aircraft. The use of kinematic design methods and tools involves the introduction of additional search radar equipment installed on a drone-operator raised into the airspace, as well as a mathematical apparatus for refined calculations of the coordinates and parameters of the spatial movements of moving objects. Thanks to this, two paired radar search systems, which are equipped with modern fast-acting computing equipment, as well as appropriate software, are able to unmistakably "screen out" false return electromagnetic signals. This is what makes it possible to reliably isolate the sought-after moving object and subsequently clearly track its movement in space. The corresponding mathematical dependencies are proposed for refined calculations of the parameters of spatial movements of moving objects and their instantaneous coordinates. Including for calculations of the distance of a moving object to radar stations, its coordinates in the introduced orthogonal coordinate systems, speed and acceleration of movement, etc. All this makes it possible to increase the efficiency of detecting enemy sabotage, reconnaissance and strike unmanned aerial vehicles, including Iranian-made drones of the Sahed-136 model.